pecifics for generalists: Teaching elementary physical education - Chunlei Lu; Amanda De Lisio (International Electronic Journal of Elementary Education, 2009)
Quality physical education offered at the elementary school level is critical for children to understand and develop healthy living. In most countries, physical education is taught by a generalist teacher (i.e., an individual who has not undertaken extensive training in physical education) particularly at the elementary school level. Inadequate and inappropriate preparation has been identified as a major barrier for an elementary generalist to develop and implement a quality physical education program. The purpose of this paper is to identify and discuss helpful strategies used to employ each fundamental component of a quality physical education program and is intended for a generalist audience. More specifically, the paper will explore (a) the (dis)advantage of teaching physical education as a generalist teacher; (b) the ability of physical education to address the whole child; (c) the confusion surrounding physical education and physical activity; and (d) the strategies of a successful physical educator.